Genetic variation in small proline rich protein 2B as a predictor for asthma among children with eczema - Epstein, Tolly G. (2012)
BACKGROUND: Small proline rich protein 2B (SPRR2B) is a skin and lung epithelial protein associated with allergic inflammation in mice that has not been evaluated in human atopic diseases. OBJECTIVE: To determine whether single-nucleotide polymorphisms (SNPs) in SPRR2B are associated with childhood eczema and with the phenotype of childhood eczema combined with asthma. METHODS: Genotyping for SPRR2B and filaggrin (FLG) was performed in 2 independent populations: the Cincinnati Childhood Allergy & Air Pollution Study (CCAAPS; N = 762; birth-age, 4 years) and the Greater Cincinnati Pediatric Clinical Repository (GCPCR;N = 1152; ages 5–10 years). Eczema and eczema plus asthma were clinical outcomes based on parental report and clinician’s diagnosis. Genetic analyses were restricted to whites and adjusted for sex in both cohorts and adjusted for environmental covariates in CCAAPS. RESULTS: Variants in SPRR2B were not significantly associated with eczema in either cohort after Bonferroni adjustment. Children from both cohorts with the CC genotype of the SPRR2B rs6693927 SNP were at 4 times the risk for eczema plus asthma (adjusted odds ratio, 4.1; 95% confidence interval, 1.5– 10.9; P = .005 in CCAAPS; and adjusted odds ratio, 4.0; 95% confidence interval, 1.8 –9.1; P <.001 in the GCPCR), however. SNPs in SPRR2B were not in strong linkage disequilibrium with the R501X and del2282 FLG mutations, and these findings were independent of FLG. CONCLUSIONS: An SNP in SPRR2B was predictive of asthma among white children with eczema from 2 independent populations. SPRR2B polymorphisms may serve as important predictive markers for the combined eczema plus asthma phenotype.